Elective course “Climate-sensitive health counselling” - prevention as an opportunity for people and planet? An interactive, student-led project focusing on prevention and agency in physician’s climate communication - Fülbert, Hannah; Schäfer, Louis N.; Gerspacher, Laura M.; Bösner, Stefan; Schut, Christina; Krolewski, Ralph; Knipper, Michael; Justus Liebig University Giessen (My University, 2023)
Objective: According to the WHO, anthropogenic climate change poses the greatest threat to human health in the 21st century. However, the link between climate change and human health is not an integral part of medical education in Germany. Within a student-led project, an elective clinical course was designed and successfully implemented, which has been made accessible to undergraduate medical students at the Universities of Giessen and Marburg. The implementation and didactic concept are explained in this article. Methodology: In a participatory format, knowledge is imparted using an action-based, transformative approach. Topics discussed are, amongst others, interactions of climate change and health, transformative action, and health behavior, as well as “green hospital” and the simulation of a “climate-sensitive health counselling”. Lecturers from different disciplines within and beyond medicine are invited as speakers. Results: Overall, the elective was evaluated positively by the participants. The fact that there is a high demand among students for participation in the elective, as well as for the transfer of concepts underlines the need for including this topic into medical education. The implementation and further development of the concept at two universities with different study regulations demonstrates its adaptability. Conclusion: Medical education can raise awareness of the multiple health consequences of the climate crisis, can have a sensitizing and transformative effect on various levels, and can promote climate-sensitive action ability in patient care. In the long term, however, these positive consequences can only be guaranteed by including mandatory education on climate change and health in medical curricula.
Wahlfach Klimasprechstunde - Prävention als Chance für Mensch und Planet? Ein interaktives, studentisch geleitetes Projekt mit Fokus auf Prävention und Handlungsfähigkeit in der ärztlichen Klimakommunikation
Keywords: climate change; global warming; carbon footprint; conservation of natural resources; sustainable development; global health; primary prevention; health communication; undergraduate medical education; planetary health; ddc:610